Molecular tracers preserved in Lower Jurassic "Blanowice brown coals" from southern Poland at the onset of coalification: Organic geochemical and petrological characteristics. (December 2016) - Rybicki, Maciej; Marynowski, Leszek; Misz-Kennan, Magdalena; Simoneit, Bernd R.T.
Highlights: Biomolecules are present in Lower Jurassic coal extracts. Evidence for wildfires or peat fires in Pliensbachian–Toarcian coals. Free dicarboxylic acids are common in Blanowice sub-bituminous coal. Long-term temperature increased %Ro but no influence on biomarkers and biomolecules. Abstract: The petrographic and molecular characteristics of the Pliensbachian–Toarcian "Blanowice brown coals" and associated sediments are described. These coals are generally dominated by vitrain macerals, although in one sample the inertinite is > 60%. This is interpreted as a result of wildfire or peat fire activity which was confirmed by the co-occurrence of charcoal fragments and elevated relative concentrations of unsubstituted PAHs in the samples. Vitrinite reflectance values are in the range of 0.49–0.56 %Ro and the C content varies from 30.3–61.9%, placing the coals within the sub-bituminous coal group. However, detailed characterization of coal extracts revealed their highly immature character, based on the occurrence of phenolic abietanes such as ferruginol, sugiol and 7-oxototarol, as well as other biomolecules including labdanoic acid, cholesterol and sitosterol. This is one of the first descriptions of natural product compounds in Jurassic sedimentary rocks. Moreover, in addition to typical lignin decomposition products, dicarboxylic acids with a preponderance of succinic acid were identified. To the best of our knowledge free dicarboxylic acids have not been reported previously from coal extracts. These acids are characteristic resin constituents. We speculate that a low (ca. 40–50 °C), but long-term, temperature influence led to an increased vitrinite reflectance values ca. 0.55 %Ro, with only minor changes to the composition of unstable biomarkers and biomolecules. Moreover, the resin matrix could protect unstable compounds against geochemical structural alteration. Vitrinite reflectance values may also be elevated due to oxidation which caused paler in colour reaction rims. The presence of phenolic abietanes and the absence of abietic and dehydroabietic acids suggest that the Cupressaceae and/or Podocarpaceae families were the most likely peat-forming plant species.